2013
DOI: 10.1016/j.tox.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a p53 allele delays nitrogen mustard-induced early apoptosis and inflammation of murine skin

Abstract: Bifunctional alkylating agent sulfur mustard (SM) and its analog nitrogen mustard (NM) cause DNA damage leading to cell death, and potentially activating inflammation. Transcription factor p53 plays a critical role in DNA damage by regulating cell cycle progression and apoptosis. Earlier studies by our laboratory demonstrated phosphorylation of p53 at Ser15 and an increase in total p53 in epidermal cells both in vitro and in vivo following NM exposure. To elucidate the role of p53 in NM-induced skin toxicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…In the present study therefore, the role of MPO in these important events leading to NM-induced skin pathology was analyzed using MPO KO mice. Similar to earlier reports with SM and to our previous studies with CEES and NM, NM exposure in WT mice caused a robust NM-induced increase in neutrophil infiltration and MPO activity (Blank et al, 2000; Inturi et al, 2013; Jain et al, 2011b; Millard et al, 1997; Tewari-Singh et al, 2009; Vavra et al, 2004). However, this NM-induced increase in MPO activity was not observed in MPO KO mice confirming these mice were suitable for this study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study therefore, the role of MPO in these important events leading to NM-induced skin pathology was analyzed using MPO KO mice. Similar to earlier reports with SM and to our previous studies with CEES and NM, NM exposure in WT mice caused a robust NM-induced increase in neutrophil infiltration and MPO activity (Blank et al, 2000; Inturi et al, 2013; Jain et al, 2011b; Millard et al, 1997; Tewari-Singh et al, 2009; Vavra et al, 2004). However, this NM-induced increase in MPO activity was not observed in MPO KO mice confirming these mice were suitable for this study.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies in mice have shown a profound increase in neutrophil infiltration and MPO activity in skin after dorsal exposure with CEES and NM at 12 h and 24 h time points (Inturi et al, 2013; Jain et al, 2011b; Tewari-Singh et al, 2009). To further investigate the role of the neutrophil-derived MPO enzyme in NM-induced skin injury, we employed a genetic approach using MPO KO mice where neutrophil infiltration and MPO activity were determined following NM exposure.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Their interaction with nucleic acids in DNA causes the formation of nonfunctional adducts and interstrand crosslinks resulting in DNA damage, which is the major lesion causing direct cytotoxicity or triggering downstream repair and/or cell death signaling pathways (Brimfield et al, 2009; Kehe and Szinicz, 2005). Studies with vesicating agents have shown that DNA damage and epidermal cell death involve the activation of p53-related signaling and DNA damage repair pathways, poly (ADP-ribose) polymerase (PARP), and calmodulin pathway (Inturi et al, 2013; Kehe et al, 2008; Korkmaz et al, 2006; Minsavage and Dillman, 2007; Rebholz et al, 2008; Ruff and Dillman, 2007; Tewari-Singh et al, 2010). Several reports indicate that SM exposure-induced skin toxic effects and DNA damage are associated with enhanced production of inflammatory cytokines including TNF α and chemokines, and increased oxidative stress as well nitric oxide production (Das et al, 2003; Kehe and Szinicz, 2005; Mukhopadhyay et al, 2006; Paromov et al, 2007), which could stimulate injury and escalate inflammatory responses (Kehe and Szinicz, 2005; Ruff and Dillman, 2007).…”
Section: Introductionmentioning
confidence: 99%